Strategic Integration of Information Technology in Human Resource Management: a Pathway to Industry 4.0 and Society 5.0 Synergy - Maulana, Bobby Akbar; Yunus, Muhammad; Fakhriyah, Siti Elfa; Khuzaini, Khuzaini; Shaddiq, Syahrial (Hut Publication Business and Management, 2024)
The strategic integration of Information Technology (IT) in Human Resource Management (HRM) is pivotal in navigating the transformative landscapes of Industry 4.0 and Society 5.0. This study explores the intricate connections between IT and HRM, emphasizing the synergistic pathway forged amidst the convergence of smart technologies and human-centric solutions. Insights from seminal works such as "Competing on Talent Analytics" and "The Digital Transformation of Innovation and Entrepreneurship" underscore the redefined role of HRM and the challenges associated with digital transformation. The research contributes valuable insights for academia, industry practitioners, and policymakers, offering a roadmap for organizations to effectively leverage IT integration. By fostering continuous skill development, addressing ethical considerations, and cultivating an agile organizational culture, organizations can position themselves for success in the dynamic interplay between technology and humanity.